A hierarchical search algorithm for discrete element method of greatly differing particle sizes - Peters, John F.; Kala, Raju; Maier, Robert S. (Engineering computations, 2009)
Purpose - A critical step toward an efficient contact detection algorithm is to localize the contact search to the immediate neighborhood of each particle. In particular, cell-based algorithms are simple and require O(N) computations but become inefficient when the particles are not roughly the same diameter. The purpose of this paper is to describe a hierarchical search method with the simplicity and efficiency of the neighbor search algorithm but which is insensitive to size gradation.Design methodology approach - In this method, particles are allocated to cells based on their location and size within a nested hierarchical cell space. Contact searches are limited to neighboring particles of equal size within their own hierarchy and occasionally with particles of larger size when no contacts are found within their own hierarchy.Findings - The method is shown to be effective for the most severe case of highly segregated particle distributions in which a large particle is surrounded by particles of much smaller size.Originality value - This paper is of value in concentrating on particular issues in implementing the hierarchical contact detection algorithm in a parallel computing environment using message-passing interface.